PENGARUH PENGGUNAAN MEDIA SOSIAL TERHADAP SIKAP SISWA MELAKUKAN TINDAKAN BULLYING DALAM PERSPEKTIF KEBHINNEKAAN: Studi Kasus Kelas IX SMP Negeri 35 Percut Sei Tuan - Sijabat, Yosua Gabe Maruli; Siahaan, Parlaungan Gabriel; Purba, Novridah Reanti; Gajahmanik, Shelly Elprida; Taufik, Taslima Amelia (Universitas Methodist Indonesia, 2023)
The purpose of this research is to find out the impact of the use of Social Media that has influenced students towards bullying and to find out the extent of students' understanding in respecting differences and diversity so that bullying does not occur. this research uses descriptive methods by conducting interviews with respondents of one class of students of SMP Negeri 35 Medan. The results of the research conducted are that these students already have a good attitude in using social media and students also understand how to respect diversity and not commit acts of bullying on social media.